2021
DOI: 10.1177/23259671211023803
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Bankart Repair Versus Open Latarjet for First-Time Dislocators in Athletes

Abstract: Background: In athletes with a first-time shoulder dislocation, arthroscopic Bankart repair (ABR) and the open Latarjet procedure (OL) are the most commonly utilized surgical procedures to restore stability and allow them to return to play (RTP). Purpose: To compare the outcomes of ABR and OL in athletes with a first-time shoulder dislocation. Study Design: Cohort study; Level of evidence, 3. Methods: We performed a retrospective review of patients with first-time shoulder dislocation who underwent primary ABR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Although the SIRSI score has been reported in the literature, 5,12,14-16,26 only some studies analyzed its association with return to sports. 12,14-16 Hurley et al 14 found that patients who did not return to sports after ABR showed lower mean SIRSI scores than those who returned to sports (39.8 vs 68.9, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the SIRSI score has been reported in the literature, 5,12,14-16,26 only some studies analyzed its association with return to sports. 12,14-16 Hurley et al 14 found that patients who did not return to sports after ABR showed lower mean SIRSI scores than those who returned to sports (39.8 vs 68.9, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Although the SIRSI score has been reported in the literature, 5,12,14-16,26 only some studies analyzed its association with return to sports. 12,14-16 Hurley et al 14 found that patients who did not return to sports after ABR showed lower mean SIRSI scores than those who returned to sports (39.8 vs 68.9, respectively). Moreover, Bohu et al 5 found that the likelihood of return to sports after a Latarjet procedure was significantly associated with preoperative SIRSI scores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 Although a myriad of management options exist, the open Latarjet (OL) procedure has emerged as the procedure of choice for many, with recent consensus guidelines recommending its use in cases of recurrent shoulder instability in patients with >15% glenoid bone loss. [7][8][9][10][11] The OL procedure has previously been reported to result in excellent clinical outcomes in the short term, with high rates of return to play (RTP) and low recurrence rates at medium-term follow-up, 10,[12][13][14][15][16][17] with the procedure being increasingly performed using an arthroscopic technique. [18][19][20][21] Furthermore, a systematic review of 845 shoulders by Hurley et al 22 reported excellent clinical outcomes at a 10-year follow-up post-OL procedure.…”
Section: Introductionmentioning
confidence: 99%
“… 15 As both arthroscopic Bankart repair (ABR) and open Latarjet (OL) procedures have been shown to result in excellent clinical outcomes in the long term, collision athletes often elect for surgical stabilization in the setting of anterior shoulder instability. 11 , 12 , 13 , 20 …”
mentioning
confidence: 99%